Evaluating the pedagogical effectiveness of instructional media in Arabic language education: evidence from eighth-grade Arabic schools in Brunei Darussalam - Yani, Achmad; Haji Ahmad, Siti Sara; Haji Abdullah, Hajah Rafidah; Hj Abdul Karim, Norhayati; Mohamed Abdelgelil, Mohamed Fathy; Seff, Faisal Mubarak; Sahrir, Muhammad Sabri; Husain, Muhammad Zakir; Haji Abdullah, Hajah Rafizah; Mohamed Mousa, Abdelnaser Abdelgalil (WSEAS Press, 2026)
This study evaluates the availability and pedagogical utilization of instructional media in teaching Arabic in Grade Eight Arabic schools in Brunei Darussalam. Grounded in contemporary perspectives on communicative language teaching and technology-enhanced language learning, the research seeks to examine the extent to which instructional resources support the development of Arabic language skills among students. A mixed-methods research design was employed in order to obtain a comprehensive understanding of instructional practices. Quantitative data were collected through a structured questionnaire administered to 200 Grade Eight students using a five-point Likert scale, while qualitative insights were obtained through semi-structured interviews with fifteen Arabic language teachers, classroom observations, and document analysis. The findings reveal that instructional media are generally available at a moderate to high level across the examined schools, with weighted percentages exceeding seventy percent in most dimensions. Audio materials, multimedia resources, digital tools, and language laboratories appear to be relatively accessible and contribute significantly to enhancing listening and reading skills. However, the study also identifies notable disparities in the pedagogical integration of these resources. In particular, instructional media are less frequently employed in developing speaking and writing competencies. Qualitative evidence suggests that these limitations are associated with variations in technological infrastructure, limited teacher training in digital pedagogy, and institutional constraints. The study concludes that strengthening teachers’ technological and pedagogical competencies, alongside expanding multimedia learning resources, is essential for improving the effectiveness of Arabic language education and promoting balanced development of the four language skills